LEGAL AND COMPLIANCE RISKS OF NEW TECHNOLOGIES - Yasemin Güllüoğlu; Fatih Erdemir (Ankara Sosyal Bilimler Üniversitesi Hukuk Fakültesi Dergisi)
Technology is developing parabolically. This development affects businesses' way of conduct. Both internal and external processes of enterprises are digitalized in order to increase efficiency and flexibility. Yet, the digitalization creates a variety of vulnerabilities and new legal and compliance risks. Some of these risks may arise directly from the technological tools used, for example, from a software. Some risks arise due to the features of these technological tools. For example, being vulnerable to cyber-attacks, hosting artificial intelligence. Some technological risks, on the other hand, may be caused by the characteristics of technological tools as well as the lack of awareness of the employees using these tools. The aim of this study is to address some of the legal and compliance risks that arise with technological developments and to suggest precautions that can be taken against these risks. In this context, first of all, the digitalization of enterprises will be briefly mentioned, then examples of the risks arising with digitalization will be given, and finally, some general recommendations will be made based on the measures that can be taken against these risks.